Параметрический синтез оптимальной системы наведения и стабилизации танковой пушки - Александрова, Татьяна Евгеньевна; Истомин, Александр Евгеньевич (НТУ "ХПИ", 2016)
Розглядається задача параметричного синтезу стабілізатора танкової гармати, що забезпечує максимальні значення показників стійкості, швидкодії і точності замкнутої системи наведення і стабілізації.

This article provides the problem of parametric synthesis of the stabilizer tank gun, ensuring maximum values of sustainability indicators, speed and accuracy of a closed system of guidance and stabilization.
Parametric synthesis of optimal systems of guidance and stabilization tank gun
Keywords: замкнутая система стабилизации; устойчивость; система автоматического управления; быстродействие; матрица; варьируемые параметры